Manufacturing GMP-grade mRNA vaccine-associated Enzymes: Bioprocess Development and Economics - Nyikadzawanda, Hudson (Stellenbosch : Stellenbosch University, 2026)
Thesis ( MEng)--Stellenbosch University, 2026.